Developing A Local Wisdom-based Interactive Flipbook with the Problem-based Learning Model to Enhance Critical Thinking Skills - Nora Sara Damayanti; Eko Handoyo; Suratno Suratno (Journal of Primary Education, 2022)
Less varied and less integrated learning materials with technology causing students had limited learning materials and coverage. Thus, the local wisdom-based interactive flipbook developed in this study was expected to provide learning materials and real problems so that students are encouraged to respond critically and finally have their critical thinking ability improved. Further, this study aimed to develop, analyze the feasibility, and examine the effectiveness of a local wisdom-based interactive flipbook with a problem-based learning model on the social science subject taught to grade five at SDN 1 Bandengan Jepara. It belonged to Research and Development (R&D) as developed by Brog and Gall. In addition to data collection technqiues, tests, observations, interviews, questionnaires, and documentation were employed. Once the data were collected, those were analyzed using several initial tests, namely product viability and response questionnaire, while the final data analyses covered normality test, t-test, and n-gained test. Here, 40 students of grade five at SDN 1 Bandengan Jepara were involved as the population of this study. Findings showed that the viability of this product in each aspect was presentation 100%, content was 95.31%, and language was 93.75%. In terms of effectiveness, it gained the value of sig. (2-tailed) of 0.000 <0.05 in t test, meaning that there was a significant difference between the results of the pretest and posttest with the n-gain test of 0.454 in the medium category. To sum up, the local wisdom-based interactive flipbook is viable and effective to use in social science learning.